Nexus Between Tax Revenue and Economic Growth in Nepal (Pragyaratna प्रज्ञारत्न, 2024)
This study examines the relationship between Nepal's economic growth and tax revenue from the country's fiscal years 2002–2003 to 2022–2023. Relevant time series secondary data were gathered from the World Bank, Nepal Rastra Bank, Ministry of Finance, Inland Revenue Department, and other sources in order to achieve the objectives. Scholarly publications from the past were also consulted. The linear regression model has been used to examine the gathered data. The outcome demonstrates that overall revenue, including tax revenue, significantly increases GDP. Although tax collection has shown encouraging trends, it is still insufficient to cover Nepal's government's expenses.